Dimensionamento do mercado de banda larga no Brasil - Alexandre Ywata de Carvalho; Mário Jorge Cardoso de Mendonça; José Jaime da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– The objective of this study is to predict the potential broadband market in Brazil. This task is done by combining information from two national databases: the Demographic Census of 2010 and the National Survey by Household Sample (Pnad) of 2015. The Pnad 2015 is used to estimate the probability of the household accessing internet by broadband technology using a logit regression. The broadband market is predicted using the estimated model with the same covariates found in the Demographic Census 2010. The prediction indicated a potential market of 45 million households, an additional of 6 million households in relation to the current situation. The new size of the broadband market is estimated if there is a 10% increase in the average penetration of broadband services in the main metropolitan regions. In this scenario, it is observed that the new market reaches 50,7 million households.
Keywords: L51; L96; 330; broadband; internet; logit regression; potential market; prediction